2018
DOI: 10.3390/cryst8050212
|View full text |Cite
|
Sign up to set email alerts
|

Peak Broadening Anisotropy and the Contrast Factor in Metal Alloys

Abstract: Diffraction peak profile analysis (DPPA) is a valuable method to understand the microstructure and defects present in a crystalline material. Peak broadening anisotropy, where broadening of a diffraction peak doesn't change smoothly with 2θ or d-spacing, is an important aspect of these methods. There are numerous approaches to take to deal with this anisotropy in metal alloys, which can be used to gain information about the dislocation types present in a sample and the amount of planar faults. However, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 108 publications
(238 reference statements)
3
25
0
Order By: Relevance
“…The use of polycrystal plasticity models to predict diffraction peak broadening [4,14,28,29] is a less developed modelling route than for texture or lattice strains. In this method a polycrystal plasticity model is used to predict the activity of different slip systems in different grains, this is converted to broadening by an assumption on the relationship between slip activity and dislocation density.…”
Section: Powder Diffraction Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of polycrystal plasticity models to predict diffraction peak broadening [4,14,28,29] is a less developed modelling route than for texture or lattice strains. In this method a polycrystal plasticity model is used to predict the activity of different slip systems in different grains, this is converted to broadening by an assumption on the relationship between slip activity and dislocation density.…”
Section: Powder Diffraction Measurementsmentioning
confidence: 99%
“…There are two main approaches that are generally followed: powder diffraction method and crystallographic texture measurements. In the former, plastic deformation can be quantified by measuring the changes in phase fraction [1], lattice strain [2], and the quantity and arrangement of dislocations [3][4][5]; whereas the latter gives information about changes in texture [6] of the alloy and orientations of individual phases. The two approaches provide complementary information about plastic deformation but require separate experimental set-ups.…”
Section: Introductionmentioning
confidence: 99%
“…22) The measured full-widths at half maximum (FWHMs), asymmetric factors, and crystallite sizes of the PyC layers are listed Table 1. The asymmetric factors, which increase with the generation of stacking faults, 23) of P5 and P100 were calculated to be 1.27 and 1.4, respec-tively. With a decrease in FWHM values and asymmetric factors, defects like stacking faults also decrease.…”
Section: Microstructure Of the Pyc Layers Deposited On Carbon Preformsmentioning
confidence: 99%
“…Simm et al, have applied the line-profile analysis methods to investigate the dislocation character in FCC and hexagonal closed-packed alloys [26][27][28]. The results showed that heterogeneous microstructures were formed during plastic deformation in FCC nickel and stainless steel.…”
mentioning
confidence: 99%